Invention Zaman Barok dan Pengembangan Permainan Piano - RIANTI MARDALENA PASARIBU (Resital: Jurnal Seni Pertunjukan (Journal of Performing Arts), 2008)
Invention in Barok Era and The Development of Piano Lesson. In piano lesson, one material of parts towhich had been given is polyphony, which is an Invention from J.S. Invention is a basic fi nger-skill for pianist.Invention develops in the Baroque period. The baroque ideology is not only called as the reaction of Renaissance,but also as the continuing development from Renaissance. Invention is known in two forms. First is as a pianocomposition and second is as a piano play which can push a pianist to understand more about an arrangement thathe played and expressed.